We the people’s guide to estate planning : - Distenfield, Ira (Wiley, 2005)
We The People's Guide to Estate Planning makes planning for your future as painless as possible--all without the added hassle of hiring a lawyer. This practical, nuts-and-bolts guide covers all the basics of do-it-yourself estate planning, and covers everything you need to know about living trusts, wills, probate, and estate taxes. Extra resources--a glossary of estate planning terminology; a section on frequently asked questions; samples of effective living trusts and a last will and testament; as well as worksheets and essential information on how to settle an estate--make this the best resource available for this important step in planning for the future. You'll have all the information you need to understand the legal language of a will or living trust and learn how to seek state-specific laws and customs so you can tailor your plans accordingly.